Demon entrepreneurs
1 online resource
Keywords: "The 'Greek genius' appears as the combination of two stereotypes with a long pedigree: Homer's ingenious Odysseus, triumphing with tricks over his foes, and Virgil's 'deceitful Odysseus', the impostor Greek. Adamantios Korais, the leading scholar who almost single-handedly refashioned the Greek nation, fully appreciated the importance of Greek shipping and commerce, and the wealth they generated for the spread of Enlightenment ideas and the quest for political emancipation in the Greek lands. In this context, the 'genius' and the consequent economic success have long been considered the essential prerequisites for the spreading of Greek education and, ultimately, national revival. Reversely, Greek education and consciousness-building via economic success are taken as proof of the immanent 'Greek genius'. As a popular myth of redemption, this stereotype persists in a country of rather limited resources and uncertain prospects. This volume seeks to identify both the content and the ways that the 'Greek genius' has long worked at the political, social and economic level. Based on a collective research project, it offers an original contribution to the broader discussion generated by the current Greek national bicentenary. This book will appeal to all those interested in the idea of the Greek 'national character' as well as international perceptions of Greek culture, education, and society during the modern era"--